2011
DOI: 10.3354/meps09149
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton growth allometry and size- dependent C:N stoichiometry revealed by a variable quota model

Abstract: Size scaling of phytoplankton growth rates and size-dependent carbon to nitrogen (C:N) stoichiometry determine phytoplankton size structure and coupling of carbon and nitrogen cycling of marine ecosystems. They are critical in predicting the growth of phytoplankton spanning a wide range of sizes and their consequences for the biological pump in marine ecosystem models. The size scaling of phytoplankton growth and size-dependent C:N stoichiometry are modelled by embedding size-dependent light-harvesting, nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
(159 reference statements)
1
11
0
Order By: Relevance
“…Low N often limits phytoplankton growth (Mei et al 2011; Moore et al 2013; Li and Gao 2014) as indeed found here for T. pseudonana (Fig. 1a).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Low N often limits phytoplankton growth (Mei et al 2011; Moore et al 2013; Li and Gao 2014) as indeed found here for T. pseudonana (Fig. 1a).…”
Section: Discussionsupporting
confidence: 83%
“…Diatoms also span a wide size range across species from <2 µm to over 200 µm in equivalent spherical diameter, giving over eight orders of magnitude in cell volume (Beardall et al 2009) Finkel et al, 2010). Diatom cell size affects many physiological processes, including light energy absorption (Finkel 2001; Key et al 2010), photosynthesis and respiration (Wu et al 2014a; López-Sandoval et al 2014), nutrient diffusion and uptake (Raven 1998; Raven and Kübler 2002; Marañón et al 2013), and ultimately affects their growth (Mei et al 2011; Marañón et al 2013; Wu et al 2014a). …”
Section: Introductionmentioning
confidence: 99%
“…Larger phytoplankton cells are known to have slower growth rates as compared to smaller ones due to their slower biomass-normalized metabolic rates, higher nutrient/energy requirements, and faster sinking rates (Raven 1998;Raven and Kübler 2002;Mei et al 2011). However, this study reveals a new perspective to this theory that larger cells (>20 μm) can benefit from UV radiation since they can use most of UV spectral energy for photosynthesis, while smaller ones (<5 μm) cannot use this energy when PAR is limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Cell size of phytoplankton crucially determines the efficiency of element or energy transfer and, thus, the production of higher trophic levels in marine food webs (Raven 1998;Finkel et al 2010;Mei et al 2011). Light absorption (Sigee 2005;Fujiki and Taguchi 2002), photosynthesis (Raven and Kübler 2002;Li et al 2011), and tolerance to UVR (Laurion and Vincent 1998;Häder 2011) are also known to differ among differently cell-sized phytoplankton.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-optimal growth conditions, irradiance, temperature, and nutrient concentrations, can alter the size scaling of metabolism if the acquisition of resources limits metabolism and is size-dependent [5], [36], [42], [43]. Due to physical constraints larger cells will absorb fewer photons per unit of pigment than physiologically equivalent smaller cells with the same shape and intracellular pigment composition and concentration [44], [45].…”
Section: Introductionmentioning
confidence: 99%